Content Analysis of Law Number 12/2022 on Sexual Violence based on Due Diligence Framework - Poetri, Ashila Aulia; Indraswari, Indraswari; Indraswari (Contemporary Public Administration Review, 2024)
This study aims to analyze the contents of Law No. 12/2022 on Sexual Violence Crime (TPKS law). The concept used to analyze the law is the Due Diligence Framework on State Accountability in Eliminating Violence Against Women. The framework consists of five aspects: prevention, protection, prosecution, punishment, and provision of redress and reparation for victims. Through this framework, this study investigates on to what extent the TPKS Law policy can build a comprehensive system to meet the diverse, multi-aspect and multi-dimensional needs of victims of sexual violence and provide justice to htem. The method used in this study is content analysis. The results of this study shows that the TPKS Law fulfils the five aspects of the Due Diligence Framework. However, there are still several challenges, such as the mandated implementing regulations have not yet been passed, law enforcement officials’ poor perspective on gender equality, they do not have a thorough understanding regarding the TPKS Law. Therefore, this study recommends the importance to accelerate the launch of implementing regulations, law enforcement agencies have to form and/or update regulations in respective environments by adapting the provisions in the TPKS Law and accelerate the realization of related infrastructure and funding in Provinces and Regencies/Cities.